Perlambangan dalam Hiasan Tekstil Tradisional Minangkabau - Wesnina, Wesnina (SUHUF, 2009)
Traditional teaching has its impact on the creation of the art of traditional ornament of Minangkabau. That phenomenon is reflected in the effort and creation of the art designer to create traditional art motive which strictly hold to the way of life and the social and cultural system society. Traditional ornamental art of Minangkabau is a visual expression which consists of the teachings becoming the way of life of Minangkabau people in their daily life; traditional teachings and religious teachings. The philosophy of the Minangkabau tradition has its firm formation when Islam entered Minangkabau. It is reflected in the motto of the Minangkabau people in implementing their tradition and religion in their life. The motto, adat basandi syara’, syara basandi kitabullah (tradition is based the religious teachings and religious teachings are based on the Holy Book of God) is a concept which reflects that in its implementation, tradition will adjust its practice with the Islamic teachings.